Efektivitas Step Marching Exercise Dalam Mengurangi Resiko Jatuh Pada Lansia - Ramdhetya, Jabbar Naufal; Suadnyana, Ida Ayu Astiti; Novianti, IGA Sri Wahyuni; Mayun, I Gusti Ngurah (UI Scholars Hub, 2023)
As age progresses, the elderly will experience a degenerative process which one of the impacts will cause a decrease in the ability to maintain balance in the elderly so that it will increase the risk of falling. To overcome this risk, it is necessary to give exercises to improve balance and muscle strength in lower extremity, one of which is step marching exercise. This exercise has alternating leg lifting movements by following a rhythm or beat. The purpose of this study was to determine the effectiveness of step marching exercise in reducing the risk of falls in the elderly. Method: The experimental research method used pre and post test control group design using 24 respondents divided into group 1 (control / placebo) and group 2 (treatment / step marching exercise) with measuring instruments in the form of questionnaires Falls Efficacy Scale-International. The pre and post test results of both groups used the Paired Sample T-test where group 1 did not have a significant difference with a p value = 0.191 while in group 2 there was a significant difference with a p value = 0.000. In the difference test of groups 1 and 2 using the Independent Sample T-test, a significant difference was obtained with a difference value of p = 0.000. It can be concluded that step marching exercise is effective in reducing the risk of falls in the elderly